ART THERAPEUTIC TECHNOLOGIES IN THE FORMATION SUCCESSFUL PERSONALITY OF A PUPIL OF SENIOR CLASSES - Нечерда, Валерія (SWorldJournal, 2024)
The article is dedicated to the problem of art technologies that are introduced into the educational process of educational institutions. The author emphasized the indications for art therapy work with senior school pupils, the educational potential of th